Structure of a thermostable methionine adenosyltransferase from Thermus thermophilus HB27 reveals a novel fold of the flexible loop. Issue 48 (27th April 2016) - Liu, Yanhui; Wang, Wenhe; Zhang, Weiwei; Dong, Yanan; Han, Fengjiao; Raza, Muslim; Liu, Luo; Tan, Tianwei; Feng, Yue
Abstract : Methionine adenosyltransferases (MATs) are the family of enzymes which synthesize S -adenosylmethionine (AdoMet), the major biological methyl donor. Abstract : Methionine adenosyltransferases (MATs) are the family of enzymes which synthesize S -adenosylmethionine (AdoMet), the major biological methyl donor. Three-dimensional structures have been reported for MATs from several different species, including bacteria, archaea and eukarya. A common feature in MAT structures is a flexible loop which is proposed to serve as a dynamic lid controlling the access of substrate to the active site. In this study, we solved the X-ray structure of a thermostable MAT from Thermus thermophilus HB27 (TtMAT) at 2.67 Å resolution. Both the tetrameric assembly and the residues in the active site of TtMAT are similar to those of MAT from Escherichia coli (EcMAT). However, the flexible loop in TtMAT is longer than that of EcMAT and well-defined in an open conformation, which is unusual among known MAT structures. Moreover, the loop of TtMAT is in a conformation different from those of other MATs which contain ordered/disordered loops. A further analysis of this loop suggested that it might explain the better thermostability of TtMAT.